Patient safety competency and educational needs of nursing educators in South Korea. - Haena Jang; Nam-Ju Lee (PLoS ONE)
Background Nursing educators must be qualified to teach patient safety to nursing students to ensure patient safety in the clinical field. The purpose of this study was to assess nursing educators' competencies and educational needs for patient safety in hospitals and nursing schools. Method A mixed-methods sequential explanatory design employed a survey and focus group interview with nursing educators (school clinical instructors and hospital nurse preceptors). Thirty-eight questionnaires filled out by clinical instructors from six four-year nursing universities and 106 questionnaires from nurse preceptors from three high-level general hospitals in the Seoul metropolitan area were analyzed to obtain quantitative data. Focus group interviews were conducted among six clinical instructors from one nursing school and four nurse preceptors from one high-level general hospital in Seoul. Results Nursing educators had higher levels of attitude compared with relatively lower levels of skill and knowledge regarding patient safety. They reported educational needs of "medication" and "infection prevention" as being higher and "human factors" and "complexity of systems" as being lower. Nursing educators desired different types of education for patient safety. Conclusion It is necessary to enhance nursing educators' patient safety skills and knowledge by developing and providing an integrated program of patient safety, with various teaching methods to meet their educational needs. The findings of this study provide the basic information needed to reform patient safety education programs appropriately to fit nursing educators' needs and their patient safety competencies in both clinical practice and academia. Furthermore, the findings have revealed the importance of effective communication between clinical and academic settings in making patient safety education seamless.